Rapid high-resolution U-Pb LA-Q-ICPMS age mapping of zircon - Mc Evoy, Niall; Chew, David (My University, 2017)
Zircon commonly exhibits textural evidence for distinct growth events (e.g. polyphase core–rim structures) and evidence for Pb mobility not linked to discrete crystallization episodes (Pb loss, incorporation of common Pb, high-temperature Pb mobilization). Interpreting complex U–Pb zircon age data therefore requires imaging of zircon crystals and texturally-controlled sampling to constrain the fine-scale processes affecting the U–Pb zircon systematics. High-resolution U–Pb laser-ablation quadrupole inductively coupled plasma mass spectrometry (LA-Q-ICPMS) zircon age maps were undertaken on zircon sampled from syn-tectonic granitoid suites from the Peruvian Eastern Cordillera that exhibit textural evidence for clearly-defined cores and rims. The images were acquired by rastering a 7 mm spot with a 3.5 J cm 2 fluence, with scan speeds of 3 mm s 1 and a 10 Hz repetition rate (ThermoScientific iCAP-Qc setup) and scan speeds of 20 mm s 1 and a 45 Hz repetition rate (Agilent 7900 system). The mapping-experiment duration for individual zircons was as fast as 10 minutes (Agilent 7900 setup). 91500 zircon was employed as the primary reference material, and secondary-standard data (Temora, Pleˇsovice, WRS-1348, FC-1, Fish Canyon, Tardree) typically reproduce within 1% of their published crystallization ages. Zircon rim concordia ages derived from the U–Pb age maps are consistent with independent secondary ion mass spectrometry (SIMS) and thermal ionisation mass spectrometry (TIMS) constraints. Two-dimensional kernel density estimation of the combined U–Pb data from each map define clear discordia mixing lines between the rim- and core-age components, and also show Pb loss and common Pb vectors. Potential applications of the technique include the characterisation of complex polyphase zircons and characterising the U–Pb systematics of key samples for time-intensive U–Pb TIMS dating.
PUBLISHED